INTENSIFICATION OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE: MOBILE APPLICATIONS - G M Lyovina (Russian Language Studies, 2016)
The paper addresses methodological potential of mobile technologies in teaching a foreign language. The principles of creating exercises for Russian as a foreign language mobile learning at levels A1-A2 are considered in the article.